Exploration of Antibiotic Activity of Aminoglycosides, in Particular Ribostamycin Alone and in Combination With Ethylenediaminetetraacetic Acid Against Pathogenic Bacteria - Kong, Jing; Wu, Zhuo-Xun; Wei, Liuya; Chen, Zhe-Sheng; Yoganathan, Sabesan (Frontiers in Microbiology, 2020)
The emergence of infections caused by bacterial pathogens that are resistant to current antibiotic therapy is a critical healthcare challenge. Aminoglycosides are natural antibiotics with broad spectrum of activity; however, their clinical use is limited due to considerable nephrotoxicity. Moreover, drug-resistant bacteria that cause infections in human as well as livestock are less responsive to conventional antibiotics. Herein, we report the in vitro antibacterial evaluation of five different aminoglycosides, including ribostamycin, against a panel of Gram-positive and Gram-negative pathogens. Eight of the tested bacterial strains are linked to gastrointestinal infections. The minimum inhibitory concentration (MIC) of ribostamycin against three different E. coli strains is in the range of 0.9 – 7.2 μM, and against a strain of Hemophilia influenzae is 0.5 μM. We also found that the MIC of ribostamycin was considerably enhanced from 57.2 μM to 7.2 μM, an 8-fold improvement, when bacteria were treated with a combination of ribostamycin and ethylenediaminetetraacetic acid (EDTA). These findings demonstrate a promising approach to enhance the clinical potential of ribostamycin and provide a rational for its antibiotic reclassification from special level to non-restricted level.